(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
An Attempt Was Made To Apply The Survival Or Reliability Function Of Continuous Probability (Weibull Distribution) On Surviving Syrian Population Of Data During The Observational Years 2016.2017,2018,Considering 2017 As The Base Year, For The Period (1998-2017), The Survival Probabilities Were Calculated By Using (Knapp Zeuner) Method After Using ( Sprague Coefficient Table) To Break Up Five Categories Into One-Age Categories, We Estimated The Two Parameters Of The Distribution Using ( Least Square Method), And Calculated( Hazard Function). The Possibility Of Using Survival Function Was Tested By (Anderson Darling) Test, The P-Value Was Calculated. The Results Were: Predicting Survival Hazard Probability To Population In Syria By Using Weibull Distribution, There Is A Direct Effect Of Increasing Age On Hazard And Cumulative Function And Inverse Effect On Survival Function .